DEVELOPMENT OF SUNSCREEN PRODUCTS CONTAINING Stichopus hermanii Semper, 1868 - Widyowati, Ulfi; Genatrika, Erza; Djalil, Asmiyenti Djaliasrin (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Prolonged radiation from UV sunlight has been known to be responsible for skin damage. Sunscreen has been used to limit sun exposure. Sunscreen with natural ingredients has the potential to be developed along with the issue of side effects of synthetic ingredients. This study aimed to develop a zooceuticals sunscreen cream containing a Stichopus hermanii Semper, 1868 extracts. The sunscreen creams were formulated with various ingredients of extract include 0.05 (F1), 0.1 (F2), and 0.2 (F3) %, respectively. The in vitro sun protection factor, organoleptic properties, homogeneity, pH, viscosity, spreadability, and adhesion of the creams were evaluated. F3 met the requirements of physical properties. The extract show sun-protective efficacy with SPF value of 2.11 (F1), 3.09 (F2), and 3.46 (F3). Sunscreen containing 0.2% of Stichopus herrmanni extract is the most preferred formulation with minimal protection category.  Keywords: Sea Cucumber, Stichopus hermanii Semper, 1868, Sunscreen.